Protestant theology and the making of the modern German university - Howard, Thomas A. (Oxford University Press, 2006)
Theology, modernity, and the German University -- On the state and modern science 'in the German sense' -- Plan of study -- Broader considerations, or 'the pathos of modern theology' -- Sacra Facultas and the coming of German modernity -- The medieval legacy -- Humanism, the Reformation, and the universities -- The eighteenth century : decline and critique -- The way forward : Halle and Göttingen -- 'Torchbearer or trainbearer'? : the faculties and Immanuel Kant -- Theology, Wissenschaft, and the founding of the University of Berlin -- Revolutionary times and the ascendancy of Wissenschaft -- 'A new creation' -- Theology and the idea of the New University -- Early operations : Berlin's theological faculty, 1810-1819 -- 'Renewing Protestantism' : Schleiermacher and the challenge of modern theological education -- An Erastian modernity? : church, state, and education in early nineteenth-century, Prussia -- Church and state before 1806 -- The great transition : church and state after 1806 -- 'A realm of the intelligence' : Minister Altenstein and his legacy -- Theologia between science and the state -- General trends and developments, 1810-1918 -- The rise and fall of 'theological encyclopedia' -- History, commemoration, and the university -- 'The age of German footnotes' : visitors from abroad, admirers from afar -- 'The crisis of the theological faculty' : Lagarde, Overbeck, and Harnack -- Conclusion : Janus gazing